Remarks on an optimization problem for the p-Laplacian - Del Pezzo, L.M. (2010)
In this note we give some remarks and improvements on our recent paper [5] about an optimization problem for the p-Laplace operator that were motivated by some discussion that we had with Prof. Cianchi. © 2009 Elsevier Ltd. All rights reserved.